Sentencing matters - Tonry, Michael H. 1954- (Studies in crime and policy, 1996)
In Sentencing Matters, Michael Tonry, an internationally recognized authority in the field, offers a comprehensive overview of research, policy developments and practical experience concerning sentencing and sanctions. He examines the effects of increased penalties and whether America has become a safer place as a result. Tonry contends that in order for sentencing to be fair and effective, comprehensive and defensible policies must be in place and mechanisms must exist to implement those policies. He also looks at mandatory penalties, community sanctions, and sentencing changes in other countries, and proposes sentencing policies for the twenty-first century